11z-13=3z+17

Simple and best practice solution for 11z-13=3z+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11z-13=3z+17 equation:


Simplifying
11z + -13 = 3z + 17

Reorder the terms:
-13 + 11z = 3z + 17

Reorder the terms:
-13 + 11z = 17 + 3z

Solving
-13 + 11z = 17 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-13 + 11z + -3z = 17 + 3z + -3z

Combine like terms: 11z + -3z = 8z
-13 + 8z = 17 + 3z + -3z

Combine like terms: 3z + -3z = 0
-13 + 8z = 17 + 0
-13 + 8z = 17

Add '13' to each side of the equation.
-13 + 13 + 8z = 17 + 13

Combine like terms: -13 + 13 = 0
0 + 8z = 17 + 13
8z = 17 + 13

Combine like terms: 17 + 13 = 30
8z = 30

Divide each side by '8'.
z = 3.75

Simplifying
z = 3.75

See similar equations:

| y-2/3=-2/3+y | | -t+5=-19+t | | 5-3w=-16 | | 26-(4x-11)=3x-43 | | 2*4=4x | | 55x-44x-12x-12x+96=12x+99-178-66x-30 | | 2c+3=c-2 | | 3*16= | | 6-1.5y=13-5y | | -3x+x=-x+5 | | -6+5y=-26 | | 5x=9*(2x)-3*(4x)-1 | | -78+66x-21x+20-47+88x=10x-36x+18 | | -3m=8n-1 | | -5r+8=43 | | 9k-7=21-3k | | 1.7t+8-1.62=0.4t-0.32+8 | | 7h+3=0 | | 37=x+3+2x+2+5x | | m=2-1.25(-1) | | 5y-3+y=90 | | 80-3k=5k+8 | | -22+14x-33+10x-77+25x=88-14x+65-5+35 | | 2(2d-7)=(2+4d)2 | | 2x+32=6x+8 | | w^2+2w-310=0 | | 2w-9=-17 | | 5w^2+30w+6=0 | | 16x(7-x)=160 | | 8x-2=28x+13 | | 9*(3x)+4*(3x)=30x+5 | | (4x+34)=(7x+10) |

Equations solver categories